A PREVENTION PROGRAM FOR LOW BACK PAIN IN JAPANESE ELITE SWIMMERS. Issue 7 (11th March 2014) - Hangai, M; Koizumi, K; Noriyuki, T; Okuwaki, T; Kaneoka, K
Abstract : Background: It is known that lumbar disc degeneration (DD) might be associated with low back pain (LBP). Moreover, the DD rate is higher in swimmers than in other sports athletes.We have experienced several Japanese Olympic swimmers who could not show their best performance due to LBP. Objective: To investigate if the intervention by a LBP prevention program is effective for Japanese elite swimmer's performance. Design: Prospective longitudinal study. Setting: Japanese swimmers for the Beijing and London Olympics and elite national swimmers from 2009 to 2011. Participants: 57 swimmers (29 males and 28 females). Risk factor assessment: T2-weighted sagittal MR images of lumber spine were taken once a year. The degree of DD was categorized into 5 grades using the Pfirrmann's classification. Change in the grade by MR images was evaluated. The prevention program consists of 2 components. One is control of axial load training for the lumbar spine depending on their grade. The other is the implement of stability training for the lumbar spine by physical trainers to all swimmers at competitions and training camps. Main outcome measurements: Severe LBP affected the swimmer's performance in the competition during follow-up periods. Results: The DD rate of the all swimmers was 54.4%. The DD rates of Beijing and London Olympians were 51.6% and 59.3%, respectively. Severe LBP was found in 3 of 5 swimmers with aggravation of the DD grades. However, there was no swimmer who did not withdraw from the London Olympics due to LBP after the implementation of 4 years prevention program. Conclusions: Our results suggest that the swimmer's aggravation of DD grade was associated with LBP. However, although the DD rate of London Olympians was higher than that of Beijing Olympians, there was no London Olympian who could not perform due to LBP. Our study shows that the LBP prevention program may be effective in elite swimmers in terms of performance.